2021
DOI: 10.3390/pr9020394
|View full text |Cite
|
Sign up to set email alerts
|

The EU Training Network for Resource Recovery through Enhanced Landfill Mining—A Review

Abstract: The “European Union Training Network for Resource Recovery Through Enhanced Landfill Mining (NEW-MINE)” was a European research project conducted between 2016 and 2020 to investigate the exploration of and resource recovery from landfills as well as the processing of the excavated waste and the valorization of the obtained waste fractions using thermochemical processes. This project yielded more than 40 publications ranging from geophysics via mechanical process engineering to ceramics, which have not yet been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 151 publications
(179 reference statements)
0
5
0
Order By: Relevance
“…Enhanced landfill mining (ELFM) can be defined as an "innovative transformation technology" and is a promising emerging technology [73]. In the first instance, ELFM concentrates materials (metals, combustibles, and inert materials) that can be used as secondary raw materials [73]. These materials are then reused to produce valuable products, e.g., inorganic polymers.…”
Section: Remediation Vs Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced landfill mining (ELFM) can be defined as an "innovative transformation technology" and is a promising emerging technology [73]. In the first instance, ELFM concentrates materials (metals, combustibles, and inert materials) that can be used as secondary raw materials [73]. These materials are then reused to produce valuable products, e.g., inorganic polymers.…”
Section: Remediation Vs Recoverymentioning
confidence: 99%
“…Numerous studies found that the recycling avenues for inorganic-non-metallic fractions are more challenging with low application aggregate as the preferred route [75,76]. Additionally, the combustible fraction is predominantly disposed of through traditional methods, e.g., incineration, which the supplier must pay for rather than obtaining revenue [73,77].…”
Section: Remediation Vs Recoverymentioning
confidence: 99%
“…The solution: a robust integrated approach Building on the work done in the EU projects RAWFILL and NEW-MINE (e.g., Isunza Manrique et al, 2019;RAWFILL, 2021;Vollprecht et al, 2021), we propose an integrated approach to tackle the above-mentioned challenges for geophysical landfill resources evaluation in a consistent way. The broader aim is to contribute to the development of a standard workflow properly integrating geophysical and conventional site investigation methods to derive a combined conceptual site model-the standard tool in environmental site assessment-and resource distribution model (RDM)-the proposed tool for landfill resources evaluation.…”
Section: Geophysics For Evaluating Landfill Resourcesmentioning
confidence: 99%
“…Enhanced Landfill Mining (ELFM) address the combined and integrated valorisation of distinct landfilled urban waste streams as both materials (Waste-to-Materials, WtM) and energy (Waste-to-Energy, WtE) while meeting the most stringent ecological and social criteria (Jones et al, 2013). ELFM provides an opportunity for combined resource recovery and reclamation of land while mitigating future environmental liabilities and remediation costs through excavation innovative transformation technologies (Jones et al, 2013;Esguerra et al, 2021;Vollprecht et al, 2021).…”
Section: Introductionmentioning
confidence: 99%